Faktor-faktor yang Berhubungan dengan Kejadian Preeklampsia pada Ibu Bersalin di Ruangan Camar II RSUD Arifin Achmad Provinsi Riau Tahun 2014 - Novita Lusiana Sarmin (STIKes Hang Tuah Pekanbaru, 2015)
Preeklampsia is a set of symptoms that occur in pregnant women, maternity and postpartum consisting of hypertension, edema and proteinuria that appeared at 20 weeks until the end of the first week after birth. Problem in this study are the factors associated with the incidence of preeclampsia in the room Camar II Arifin Achmad Hospital Riau Province Year 2014. This study aimeds to determine the causes of the incidence of preeclampsia in Arifin Achmad Province Riau Year 2014. This research method was quantitative analytica study,with case control design, retrospective study approach. The population in this study were all women giving birth in the room Camar II were recorded in the medical record room Camar II Arifin Achmad Hospital in Riau year 2014 with a total population of 1247 deliveries. Data analysis was performed using univariate and bivariate using with chi square. The result showed that there was no correlation between age and the incidence of preeclampsia (p = 0.114), there was no correlation between the parity with the incidence of preeclampsia (p = 0.054), there was a significant relationship between heredity with preeclampsia (p = 0.000), there was in no relationship between the factor twin pregnancies with preeclampsia (p = 0.470), there was a significant relationship between history of the disease and the incidence of preeclampsia (p = 0.000). Based on the result of this study concluded that there was no relationship between age, parity, twin pregnancy with preeclampsia, there is a significant relationship between heredity, history of the disease and the incidence of preeclampsia